Burden of hereditary transthyretin amyloidosis on quality of life. Issue 2 (13th June 2019) - Yarlas, Aaron; Gertz, Morie A.; Dasgupta, Noel R.; Obici, Laura; Pollock, Michael; Ackermann, Elizabeth J.; Lovley, Andrew; Kessler, Asia Sikora; Patel, Pankaj A.; White, Michelle K.; Guthrie, Spencer D.
ABSTRACT: Introduction: Hereditary transthyretin (hATTR) amyloidosis is a progressive, degenerative disease, with peripheral neuropathy, cardiomyopathy, and other clinical manifestations. In this study we examine the impact of hATTR amyloidosis on quality of life (QOL). Methods: Neuropathy‐specific QOL, measured with the Norfolk QOL‐Diabetic Neuropathy questionnaire, was compared between patients with hATTR amyloidosis and patients with type 2 diabetes, whereas generic QOL, measured with the 36‐item Short Form Health Survey version 2 (SF‐36v2), was compared between patients with hATTR amyloidosis, the general population, and patients with chronic diseases. Results: Neuropathy‐specific QOL for patients with hATTR amyloidosis was nearly equivalent to that of patients with type 2 diabetes with diabetic neuropathy accompanied by a history of ulceration, gangrene, or amputation. Generic QOL was worse than that seen in the general population, with physical functioning worse than that for patients with multiple sclerosis and congestive heart failure. Discussion: Patients with hATTR amyloidosis show significant burden on QOL, particularly in physical functioning. Muscle Nerve 60 : 169–175, 2019